HIGH ORDER THINKING SKILL (HOTS) IN ENGLISH TEXTBOOK BAHASA INGGRIS: WORK IN PROGRESS: A CONTENT ANALYSIS - Saroinsong, Novena M. M.; Maru, Mister Gidion; Liando, Nihta V. F. (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
The purpose of this research was to analyse the activities and tasks in Bahasa Inggris: Work in Progress English textbook and determine whether high order thinking skill based on the cognitive domain of Bloom’s Taxonomy are integrated in the activities and tasks. The research design used is content analysis, with the data source being the textbook itself. The data collection technique used was content analysis and are analysed using descriptive analysis. The findings showed that all six levels of the cognitive domain in Bloom’s Taxonomy are present in the textbook’s task and activities. From the 184 activities present in the textbook, HOTS activities totals to 31% with L4 consists of 17 activities (9%), L5 consists of 18 activities (10%), lastly L6 consists of 19 activities (10%), while LOTS activities totals to 71% with L1 consists of 82 activities (45%), L2 consists of 32 activities (17%), L3 consists of 16 activities (9%). Thus, high order thinking skill (HOTS) is proven to be integrated in the activities and tasks in the textbook. The results implied that the textbook considers the internal and external factors that are affecting teachers and the current status quo of the students by integrating HOTS activities at a moderate amount as not to overwhelm the students.